Diagnostic Accuracy of Thyroid Doppler in Predicting Malignancy in Thyroid Nodules, Keeping Histopathology as Gold Standard - Ishtiaq, Bushra; Awan, Muhammad Wasim; Iqbal, Shaghaf; Zahra, Shan E; Ahmed, Raheen; Mughal, Huma Mahmood (Biological and Clinical Sciences Research Journal, 2025)
Thyroid nodules are common clinical findings with varying etiologies, ranging from benign lesions to malignant tumors. Accurate preoperative evaluation is crucial to avoid unnecessary surgeries. Doppler ultrasonography offers a non-invasive modality for assessing vascular characteristics associated with malignancy. However, its diagnostic performance varies across clinical settings. Objective: To evaluate the diagnostic accuracy of Doppler ultrasonography in detecting malignancy in thyroid nodules, using histopathological examination as the gold standard. Methods: This prospective observational study was conducted at KRL Hospital, Islamabad, from December 15, 2024, to March 15, 2025. Ethical approval was obtained from the Institutional Review Board. 150 patients (aged >18 years, both genders) with thyroid nodules identified clinically or through routine imaging were enrolled using non-probability consecutive sampling. Doppler ultrasonography was performed for all participants, followed by histopathological evaluation after surgical excision or fine-needle aspiration. Statistical analysis was carried out using SPSS v25. Sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), diagnostic accuracy, and receiver operating characteristic (ROC) curves were calculated for both modalities. Results: Doppler ultrasonography demonstrated a sensitivity of 82.6%, specificity of 77.3%, and an overall diagnostic accuracy of 80% in identifying malignant thyroid nodules. In comparison, histopathology revealed superior diagnostic metrics with a sensitivity of 97.06%, specificity of 90.24%, PPV of 89.19%, NPV of 97.37%, and diagnostic accuracy of 93%. The ROC curve analysis for histopathology confirmed high diagnostic performance with an AUC of 0.937. Conclusion: Doppler ultrasonography is a valuable, moderately accurate, and non-invasive diagnostic tool for assessing malignancy in thyroid nodules. Despite its moderate sensitivity and specificity, it remains a practical initial imaging modality, though histopathology remains the definitive diagnostic standard.